Structural and optical properties of un-doped and doped Sr3Al2O6 obtained through the tartarate precursor method. Issue 18 (15th December 2017) - Mindru, Ioana; Gingasu, Dana; Patron, Luminita; Marinescu, Gabriela; Culita, Daniela C.; Calderon-Moreno, Jose Maria; Preda, Silviu; Secu, Mihail
Abstract: Un-doped and doped strontium aluminates (Sr3 Al2 O6, Sr3 Al2 O6 :Tb 3+, Sr3 Al2 O6 :Tb 3+, Eu 3+ and Sr3 Al2 O6 :Tb 3+, Eu 3+ /Eu 2+ ) were synthesized through a soft chemical method – the tartarate precursor route. The tartarate precursors were characterized by infrared spectroscopy (IR) and thermal analysis. The strontium aluminates were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and infrared spectroscopy (IR). The XRD patterns confirmed the formation of single-phase cubic structure Sr3 Al2 O6 with average crystallite size of 18 nm. SEM micrographs showed porous polycrystalline powder microstructures and EDX analysis confirmed the incorporation of the dopant in the Sr3 Al2 O6 powders. The photoluminescence spectrum recorded on Sr3 Al2 O6 : Tb 3+, Eu 3+ (obtained from tartarate precursor calcined in air) showed the typical f-f luminescences of the RE-ions. Subsequent calcination of this sample in reducing atmosphere is accompanied by new photoluminescence and thermoluminescence features associated to the Eu 2+ ions. Graphical abstract: Highlights: Sr3 Al2 O6, SrAl2 O4 :Tb 3+, Eu 3+ /Eu 2+ were prepared by tartarate precursor method. Sr3 Al2 O6 single cubic phase with average crystallite size of 18 nm was formed. Photo- and thermoluminescence were associated to Eu 3+ /Tb 3+ -doped Sr3 Al2 O6 matrix. Reduction of Eu 3+ ions is accompanied by new photo- and thermoluminescence features.